Cytotoxic performances of new anionic cyclometalated Pt(II) complexes bearing chelated O^O ligands. (16th January 2020) - Ionescu, Andreea; Caligiuri, Rossella; Godbert, Nicolas; Ricciardi, Loredana; La Deda, Massimo; Ghedini, Mauro; Ferri, Nicola; Lupo, Maria Giovanna; Facchetti, Giorgio; Rimoldi, Isabella; Aiello, Iolinda
Abstract : The in vitro biological activity towards the MDA‐MB‐231 triple‐negative breast cancer cell line of two different series of anionic Pt(II) organometallic complexes was tested. For the first time, cytotoxic activity of anionic Pt(II) complexes has been observed. The anionic compounds of general formula NBu4 [(C^N)Pt(O^O)], where (C^N) represents the cyclometalated form of 2‐phenylpyridine (H(PhPy)), 2‐thienylpyridine (H(Thpy)) or 2‐benzo[ h ]quinoline (H(Bzq)), feature two different (O^O) chelated ligands: tetrabromocatechol [BrCat] 2− (1 –3 ) or alizarine [Aliz] 2− (4 –6 ). Complexes 1 –6 displayed a significant cytotoxic effect against the studied cell line (IC50 range of 1.9–52.8 μM). For BrCat‐containing complexes 1 –3, the biological activity was independent of the nature of the coordinated (C^N) ligand. In contrast, in the case of 4 –6, the cytotoxicity (significantly high for 4 ) was concomitantly induced by the presence of either the PhPy or the [Aliz] 2− ligand. Since complexes 1–6 are emissive in solution, the potential use of 4 as a theranostic agent was investigated using confocal analysis. The fluorescence signal from MDA‐MB‐231 cells incubated with 4 indicated the localization of the compound into the cytosol region. Abstract : The in vitro biological activity towards the MDA‐MB‐231 triple‐negative breast cancer cell line of two different series of anionic Pt(II) organometallic complexes was tested.